Grouting material as well as preparation method and application thereof
By using grouting materials composed of clay, industrial solid waste, etc., and forming aluminosilicate polymer structure through exciters, the problems of large cement dosage, large shrinkage, poor bonding and unenvironmental protection in traditional grouting materials in hollow repair are solved, and the advantages of good fluidity, early condensed and fast condensed, high bonding strength, and small shrinkage are achieved.
Patent Information
- Application Number
- CN202510084236.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
AI Technical Summary
In hollow repair, traditional grouting materials have problems such as large cement mixing, large shrinkage, poor adhesion, and unenvironmental protection.
The grouting material consisting of clay, industrial solid waste, cement, gypsum, excitants, admixtures and redispersible latex powder are used to dissolve the active ingredients in the industrial solid waste through the excitants to form a three-dimensional network or chain-shaped aluminosilicate polymer structure to improve bonding strength and durability.
It has achieved the advantages of good fluidity, early condensed and fast condensed, high bonding strength, small shrinkage rate, etc., and has the characteristics of early strength and fast hardness, high temperature resistance, corrosion resistance, anti-seepage and frost resistance, and good durability, and meets the requirements of green and environmental protection.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and in particular to a grouting material and a preparation method and application thereof. Background Art
[0002] During building decoration, hollowing is a common phenomenon after wall tiles and floor tiles are laid. Severe hollowing usually requires repair by opening holes and injecting grouting.
[0003] At present, grouting products used for hollow repair are mainly composed of hydraulic base materials and polymer base materials. Among them, hydraulic base materials are cement-based inorganic binders made by using fine aggregates, concrete admixtures, and other auxiliary materials. Although this type of material is relatively low in price, durable, and widely used, it has a large cement content, large shrinkage, poor adhesion, and is not environmentally friendly; polymer base materials mainly use organic polymers as binders, which have a fast hardening speed and good adhesion. They are generally used in specific scenarios, but they are relatively expensive, have poor weather resistance, and are not environmentally friendly.
[0004] Therefore, traditional grouting materials still need to be improved. Summary of the invention
[0005] Based on this, one or more embodiments of the present application provide a grouting material with good fluidity, early and fast setting, high bonding strength, and small shrinkage, as well as a preparation method and application thereof.
[0006] According to a first aspect of an embodiment of the present application, a grouting material is provided, comprising the following components in parts by mass:
[0007] 25 to 35 parts of clay, 20 to 30 parts of industrial solid waste, 5 to 15 parts of cement, 1 to 3 parts of gypsum, 5 to 10 parts of activator, 0.1 to 1 part of admixture, 1 to 5 parts of redispersible latex powder and 20 to 30 parts of water;
[0008] Wherein, the industrial solid waste includes fly ash and granulated blast furnace slag powder.
[0009] In some embodiments, the following components are included by weight:
[0010] 25 to 30 parts of clay, 25 to 30 parts of industrial solid waste, 5 to 12 parts of cement, 1.5 to 2.5 parts of gypsum, 6 to 9 parts of activator, 0.4 to 1 part of admixture, 1 to 4 parts of redispersible latex powder and 23 to 30 parts of water.
[0011] In some embodiments, the clay includes one or more of kaolin and montmorillonite.
[0012] In some of the embodiments, the mass ratio of the fly ash to the granulated blast furnace slag powder is (1-3):1.
[0013] In some of the embodiments, the cement includes one or more of ordinary Portland cement, Portland cement and rapid hardening sulphoaluminate cement.
[0014] In some of these embodiments, the gypsum includes hemihydrate gypsum.
[0015] In some embodiments, the activator includes one or more of sodium silicate and sodium carbonate;
[0016] Optionally, the activator includes sodium silicate and sodium carbonate;
[0017] Further optionally, the mass ratio of the sodium silicate to the sodium carbonate is (1-4):1.
[0018] In some embodiments, the admixture includes one or more of a high-efficiency water reducer, a defoamer, and a thickener;
[0019] Optionally, the high-efficiency water reducer includes a polycarboxylate high-efficiency water reducer;
[0020] Optionally, the defoaming agent includes a polyurethane defoaming agent;
[0021] Optionally, the thickener comprises a polycarboxylate thickener.
[0022] According to a second aspect of an embodiment of the present application, a method for preparing a grouting material is provided, comprising the following steps:
[0023] The raw materials are provided according to the above-mentioned components of the grouting material, and mixed evenly to obtain the grouting material.
[0024] According to three aspects of the embodiments of the present application, the application of the grouting material as described above in hollow repair is provided.
[0025] Compared with the traditional technology, this application has the following beneficial effects:
[0026] The present application adopts specific types of raw materials to prepare grouting materials, and controls the mass fraction of each component within a specific range. The raw material components act synergistically and cooperate with each other. Among them, the activator can dissolve active ingredients such as silicon and aluminum in fly ash and granulated blast furnace slag powder, and the dissolved silicate ions and aluminate ions will undergo condensation reaction in an alkaline environment. They are connected to each other by sharing oxygen atoms to form a three-dimensional network or chain-like aluminosilicate polymer structure, so that the prepared grouting material has the advantages of early strength and fast hardening, high temperature resistance, corrosion resistance, impermeability and frost resistance, and good durability. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0029] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0030] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0031] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0032] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0033] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0034] In a first aspect of the embodiment of the present application, a grouting material is provided, which comprises the following components by weight:
[0035] 25 to 35 parts of clay, 20 to 30 parts of industrial solid waste, 5 to 15 parts of cement, 1 to 3 parts of gypsum, 5 to 10 parts of activator, 0.1 to 1 part of admixture, 1 to 5 parts of redispersible latex powder, and 20 to 30 parts of water;
[0036] Among them, industrial solid waste includes fly ash and granulated blast furnace slag powder.
[0037] The present application uses specific types of raw materials for preparing grouting materials, and controls clay, industrial solid waste, cement and water within a specific range. The raw material components work together and cooperate with each other, so that the grouting materials have the advantages of good fluidity, early setting and fast setting, high bonding strength, and low shrinkage. Furthermore, the industrial solid waste of the present application uses fly ash and granulated blast furnace slag powder, and the cooperation between the two can improve the bonding strength of the grouting materials.
[0038] Industrial solid wastes such as granulated blast furnace slag powder and fly ash contain a large amount of active components such as silicon (Si) and aluminum (Al), but they are usually in a relatively stable state. The addition of activators will destroy the chemical bonds on the surface of industrial solid waste particles, causing active components such as silicon and aluminum to dissolve and form silicate ions (SiO4 4 ⁻), aluminate ions (AlO2⁻), etc. The dissolved silicate ions and aluminate ions will undergo condensation polymerization in an alkaline environment, and connect with each other through shared oxygen atoms to form a three-dimensional network or chain-like aluminosilicate polymer structure, so that the prepared grouting material has the advantages of early strength and fast hardening, high temperature resistance, corrosion resistance, impermeability and frost resistance, and good durability.
[0039] Fly ash is the fine ash collected from flue gas after coal powder is burned in coal-fired power plants; this application makes secondary use of the above fly ash and granulated blast furnace slag powder, realizes the recycling of resources, and meets the requirements of green environmental protection.
[0040] As an example, the mass fraction of clay in the grouting material can be 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, or any value within the range formed by any two of the above point values.
[0041] Furthermore, the mass fraction of clay is 25 to 30 parts.
[0042] In some embodiments, the clay includes one or more of kaolin (also known as white clay) and montmorillonite. Optionally, the clay includes kaolin.
[0043] In some embodiments, the particle size of the clay is 200 mesh to 325 mesh; as an example, the particle size of the clay can be 200 mesh, 205 mesh, 210 mesh, 215 mesh, 220 mesh, 225 mesh, 230 mesh, 235 mesh, 240 mesh, 245 mesh, 250 mesh, 255 mesh, 260 mesh, 265 mesh, 270 mesh, 275 mesh, 280 mesh, 285 mesh, 290 mesh, 295 mesh, 300 mesh, 305 mesh, 310 mesh, 315 mesh, 320 mesh, 325 mesh, or any value within the range formed by any two of the above point values.
[0044] As an example, the mass fraction of industrial solid waste in the grouting material can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, or any value within the range formed by any two of the above point values.
[0045] Furthermore, the mass fraction of industrial solid waste is 25 to 30 parts.
[0046] In some embodiments, the mass ratio of fly ash to granulated blast furnace slag powder is (1-3): 1. As an example, the mass ratio of fly ash to granulated blast furnace slag powder can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, or any value within the range formed by any two of the above ratios.
[0047] Fly ash helps to improve the state of the grouting material, while granulated blast furnace slag powder helps to improve the strength of the grouting material. Therefore, the two work together to further improve the comprehensive performance of the grouting material. When the proportion of granulated blast furnace slag powder in industrial solid waste is greater than 50%, the state of the grouting material is poor and the strength no longer increases. When the proportion of granulated blast furnace slag powder is less than 25%, the strength of the grouting material decreases significantly. Therefore, this application limits the mass ratio of fly ash and granulated blast furnace slag powder to (1~3):1. Mixing fly ash and granulated blast furnace slag powder in a specific mass ratio can further improve the strength performance of the grouting material.
[0048] As an example, the mass fraction of cement in the grouting material can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, or any value within the range formed by any two of the above point values.
[0049] Furthermore, the mass fraction of cement is 5 to 12 parts; furthermore, the mass fraction of cement is 5 to 10 parts.
[0050] In some embodiments, the cement includes one or more of ordinary Portland cement, silicate cement and rapid hardening sulphoaluminate cement.
[0051] It should be noted that Portland cement is cement with calcium silicate as the main component, and its raw materials mainly include limestone, clay and iron ore powder, etc. Ordinary Portland cement is cement with dicalcium silicate and tricalcium silicate as the main components, and its raw materials mainly include limestone, clay and iron ore powder, etc.
[0052] In some embodiments, the cement has a grade of 42.5 or above, for example, it may be silicate cement with a grade of 42.5, 42.5R, 52.5, 52.5R, 62.5 or 62.5R, ordinary silicate cement with a grade of 42.5, 42.5R, 52.5 or 52.5R, or rapid hardening sulphoaluminate cement with a grade of 42.5, 52.5, 62.5 or 72.5.
[0053] As an example, the mass fraction of gypsum in the grouting material can be 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts, 3 parts, or any value within the range formed by any two of the above point values.
[0054] Furthermore, the mass fraction of gypsum is 1.5 parts to 2.5 parts; further, the mass fraction of gypsum is 1.8 parts to 2.2 parts.
[0055] In some embodiments, the gypsum includes hemihydrate gypsum. Further, the gypsum includes α-hemihydrate gypsum.
[0056] As an example, the mass fraction of the activator in the grouting material can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, or any value within the range formed by any two of the above point values.
[0057] Furthermore, the mass fraction of the stimulator is 6 to 9 parts; further, the mass fraction of the stimulator is 7 to 8 parts.
[0058] In some embodiments, the activator includes one or more of sodium silicate and sodium carbonate.
[0059] Further, the sodium silicate includes instant sodium silicate, which is an industrial grade powdered solid sodium silicate. Further, the modulus (Ms=SiO2 / Na2O) of the instant sodium silicate is 2.8 or above.
[0060] Further, sodium carbonate includes industrial grade powdered soda.
[0061] In some embodiments, the activator includes sodium silicate and sodium carbonate; further, the mass ratio of sodium silicate to sodium carbonate is (1-4):1.
[0062] Understandably, alkaline activators are key triggering materials for geopolymer polymerization reactions. Common activators include alkaline silicates, alkaline carbonates, strong alkaline substances, etc. Among them, strong alkaline materials are expensive and highly corrosive, and are generally not used in engineering practice; alkaline silicates have a general activating effect, but they can supplement the silicate ions lacking in the activated substance, and alkaline carbonates further react with calcium hydroxide, the product of cement hydration reaction, to form strong alkaline substances, which in turn activate mineral activity and provide raw materials for the polymerization reaction of geopolymers. However, when alkaline carbonates are used alone, their activating effect is poor due to their weak alkalinity and lack of silicate ions. The present application has found through experiments that when a mixture of sodium silicate and sodium carbonate is used as an activator, the activating effect is better than that of any one alone, and the activating effect is best when the mass proportion of sodium carbonate is between 20% and 50%. Therefore, the present application limits the mass ratio of sodium silicate to sodium carbonate to (1~4):1.
[0063] As an example, the mass ratio of sodium silicate to sodium carbonate can be 1:1, 2:1, 3:1, 4:1, or any value within the range formed by any two of the above ratios.
[0064] As an example, the mass fraction of the admixture in the grouting material can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, or any value within the range formed by any two of the above point values.
[0065] Furthermore, the mass fraction of the admixture is 0.4 to 1 part; further, the mass fraction of the admixture is 0.4 to 0.7 part.
[0066] In some embodiments, the admixture includes one or more of a high-efficiency water reducer, a defoamer, and a thickener.
[0067] In some embodiments, the high-range water reducer comprises a polycarboxylate high-range water reducer.
[0068] In some embodiments, the defoaming agent includes a polyurethane-based defoaming agent.
[0069] In some embodiments, the thickener comprises a polycarboxylate thickener.
[0070] In some embodiments, the admixture includes a high-efficiency water reducing agent, a defoaming agent and a thickener. Further, the mass ratio of the high-efficiency water reducing agent, the defoaming agent and the thickener is 10:1:1.
[0071] As an example, the mass fraction of the redispersible latex powder can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, or any value within the range formed by any two of the above point values.
[0072] Furthermore, the mass fraction of the redispersible latex powder is 1 part to 4 parts; further, the mass fraction of the redispersible latex powder is 1 part to 3 parts.
[0073] It can be understood that redispersible latex powder is a water-soluble redispersible powder, which is a powder adhesive formed by spray drying of a polymer emulsion and complies with the relevant provisions of GB / T 29594-2013.
[0074] As an example, the mass fraction of water can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, or any value within the range formed by any two of the above point values.
[0075] Furthermore, the mass fraction of water is 23 parts to 30 parts.
[0076] It is understandable that the "water" in this application refers to water for concrete mixing that meets the requirements of the national standard JGJ63-2006.
[0077] In some embodiments, the total number of components in the grouting material is 100 parts by mass.
[0078] In some embodiments, the following components are included, measured by mass: 25 to 30 parts of clay, 25 to 30 parts of industrial solid waste, 5 to 12 parts of cement, 1.5 to 2.5 parts of gypsum, 6 to 9 parts of activator, 0.4 to 1 part of admixture, 1 to 4 parts of redispersible latex powder, and 23 to 30 parts of water.
[0079] The present application reasonably controls the types and mass fractions of each component, and the components cooperate with each other, so that the prepared grouting material has the advantages of good fluidity, early setting and fast setting, high bonding strength, small shrinkage, etc. It also has multiple composite properties such as cement hydration, gypsum gas hardening, and alkali-induced polymerization reaction.
[0080] Compared with traditional cement-based and polymer-based grouting materials, the grouting material of the present application contains only a small amount of cement in its raw materials and does not contain toxic and harmful organic polymers. Its main components are clay and industrial solid waste, and it has the characteristics of being green and environmentally friendly.
[0081] The grouting material of the present application has the characteristics of early strength and rapid hardening, high temperature resistance, corrosion resistance, impermeability and frost resistance, and good durability due to its unique spatial three-dimensional network bonding structure.
[0082] In a second aspect of the present application, a method for preparing a grouting material is provided, comprising the following steps:
[0083] The grouting material is prepared by providing raw materials according to the components of the grouting material of the first aspect, mixing them evenly, and obtaining the grouting material.
[0084] In some embodiments, the mixing is carried out by stirring.
[0085] In some embodiments, the preparation method of the grouting material comprises the following steps:
[0086] Mixing clay, industrial solid waste, cement and redispersible latex powder uniformly to prepare component A;
[0087] The gypsum, the activator and the admixture are uniformly mixed to prepare component B;
[0088] Component A, component B and water are mixed to prepare a grouting material.
[0089] It is understandable that in order to avoid deterioration caused by mutual reaction between components during storage, the above components can be grouped according to physical and chemical properties to obtain component A and component B, and component A and component B can be stored separately in a waterproof and sealed manner.
[0090] The third aspect of the implementation mode of the present application provides the application of the above-mentioned grouting material in hollow repair.
[0091] In some embodiments, the application of the above-mentioned grouting material in hollow repair comprises the following steps:
[0092] Find the grouting port in the hollow area and clean up the accumulated water and dust near the hollow area;
[0093] Use a pinhole grouting device to inject the grouting material into the hollow drum from the grouting port until the slurry overflows, pull out the grouting device and block the grouting port.
[0094] In some embodiments, the grouting openings may be brick joints or micro holes.
[0095] In some embodiments, the following step is also included: checking the hollowing repair status 24 hours after the grouting is completed.
[0096] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0097] Example 1
[0098] (1) Weigh the following raw materials by mass: 35 parts of clay, 20 parts of industrial solid waste, 5 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.4 parts of admixture, 1 part of redispersible latex powder, and 28.6 parts of water, a total of 100 parts.
[0099] Among them, clay is selected from powdered white mud with a mass ratio of 200 to 325 mesh; industrial solid waste is selected from a mixture of fly ash and granulated blast furnace slag powder in a mass ratio of 2:1; cement is selected from silicate cement with a grade of 42.5; gypsum adopts α-type semi-hydrated gypsum for construction; the activator is selected from a mixture of instant sodium silicate and industrial grade soda in a mass ratio of 3:1; the admixture includes a high-efficiency water reducer, a defoamer and a thickener in a mass ratio of 10:1:1; and the redispersible latex powder is selected from SWF-04 type of Shanxi Sanwei Group.
[0100] (2) Mix and stir the above components except water, then add water and continue stirring to prepare a grouting material.
[0101] Example 2
[0102] The method is basically the same as Example 1, except that the weight percentage of each raw material is different. Specifically, Example 2 includes the following raw materials: 35 parts of clay, 20 parts of industrial solid waste, 7.5 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.5 parts of admixture, 1 part of redispersible latex powder, 26 parts of water, a total of 100 parts. The remaining steps and parameters are the same as those of Example 1.
[0103] Example 3
[0104] The method is basically the same as Example 1, except that the weight percentage of each raw material is different. Specifically, Example 3 includes the following raw materials: 35 parts of clay, 20 parts of industrial solid waste, 10 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.6 parts of admixture, 1 part of redispersible latex powder, 23.4 parts of water, a total of 100 parts. The remaining steps and parameters are the same as those of Example 1.
[0105] Example 4
[0106] The method is basically the same as Example 1, except that the weight percentage of each raw material is different. Specifically, Example 4 includes the following raw materials: 30 parts of clay, 25 parts of industrial solid waste, 7.5 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.5 parts of admixture, 1 part of redispersible latex powder, and 26 parts of water, totaling 100 parts. The remaining steps and parameters are the same as those in Example 1.
[0107] Example 5
[0108] The method is basically the same as Example 1, except that the weight percentage of each raw material is different. Specifically, Example 5 includes the following raw materials: 25 parts of clay, 30 parts of industrial solid waste, 7.5 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.5 parts of admixture, 1 part of redispersible latex powder, and 26 parts of water, totaling 100 parts. The remaining steps and parameters are the same as those in Example 1.
[0109] Example 6
[0110] The method is basically the same as Example 1, except that the weight percentage of each raw material is different. Specifically, Example 6 includes the following raw materials: 30 parts of clay, 25 parts of industrial solid waste, 7.5 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.6 parts of admixture, 2 parts of redispersible latex powder, and 24.9 parts of water, totaling 100 parts. The remaining steps and parameters are the same as those in Example 1.
[0111] Example 7
[0112] The method is basically the same as Example 1, except that the weight percentage of each raw material is different. Specifically, Example 7 includes the following raw materials: 30 parts of clay, 25 parts of industrial solid waste, 7.5 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.7 parts of admixture, 3 parts of redispersible latex powder, and 23.8 parts of water, totaling 100 parts. The remaining steps and parameters are the same as those of Example 1.
[0113] Example 8
[0114] The method is basically the same as Example 1, except that the type of the activator is different. Specifically, 8 parts of a mixture of 8 parts of instant sodium silicate and industrial grade soda are replaced by 8 parts of instant sodium silicate in Example 8. The remaining steps and parameters are the same as those in Example 1.
[0115] Example 9
[0116] The method is basically the same as Example 1, except that the mass ratio of fly ash to granulated blast furnace slag powder is different. Specifically, the mass ratio of fly ash to granulated blast furnace slag powder in Example 9 is 4:1. The remaining steps and parameters are the same as those in Example 1.
[0117] Comparative Example 1
[0118] The method is basically the same as Example 1, except that the weight percentage of each raw material is different. Specifically, Comparative Example 1 includes the following raw materials: 20 parts of clay, 35 parts of industrial solid waste, 7.5 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.5 parts of admixture, 1 part of redispersible latex powder, and 26 parts of water, totaling 100 parts. The remaining steps and parameters are the same as those of Example 1.
[0119] Comparative Example 2
[0120] The method is basically the same as Example 1, except that the weight percentage of each raw material is different. Specifically, Comparative Example 3 includes the following raw materials: 40 parts of clay, 15 parts of industrial solid waste, 7.5 parts of cement, 2 parts of gypsum, 8 parts of activator, 0.5 parts of admixture, 1 part of redispersible latex powder, and 26 parts of water, totaling 100 parts. The remaining steps and parameters are the same as those in Example 1.
[0121] Comparative Example 3
[0122] The method is basically the same as Example 1, except that the type of industrial solid waste is different. Specifically, 20 parts of fly ash are used to replace 20 parts of a mixture of fly ash and granulated blast furnace slag powder in Comparative Example 3. The remaining steps and parameters are the same as those in Example 1.
[0123] The mass fractions of each component in Examples 1 to 9 and Comparative Examples 1 to 3 are shown in the following table.
[0124] Table 1
[0125]
[0126] The grouting materials prepared in the above embodiments and comparative examples were subjected to performance tests. Specifically, the truncated cone fluidity was tested in accordance with GB / T 50448-2015, the initial setting time was tested in accordance with GB / T 1346-2011, the tensile bond strength was tested in accordance with JC / T 547-2017, and the vertical expansion rate was tested in accordance with GB 50119-2013. The test results are shown in the following table.
[0127] Table 2
[0128]
[0129] Compared with Example 1, in Example 8, only sodium silicate is added as an activator, but the activating effect of sodium silicate on the raw material is not as good as that of the composite activator, which reduces the tensile strength of the grouting material and reduces the volume expansion effect of the clay polymerization reaction.
[0130] It can be seen from Examples 1 and 9 that increasing the specific gravity of fly ash is beneficial to improving the state of the slurry and increasing the fluidity, but is not conducive to the development of tensile strength. It can be seen from Example 1 and Comparative Example 3 that the grouting material prepared using a single type of industrial solid waste has a significantly longer initial setting time and a lower tensile bonding strength.
[0131] It can be seen from Examples 2, 4, and 5 in the above table that as the mass content of clay decreases, the initial truncated cone fluidity of the grouting material increases and the tensile bonding strength decreases; it can be seen from Examples 4, 6, and 7 that as the mass content of the redispersible latex powder increases, the initial truncated cone fluidity of the grouting material decreases and the tensile bonding strength increases. Therefore, in order to make the grouting material have good fluidity and tensile bonding strength, the mass content of clay and redispersible latex powder needs to be controlled within the scope of this application.
[0132] It can be seen from Examples 2, 4, and 5 that as the mass content of clay decreases, the initial setting time of the grouting material is prolonged; by comparing Examples 1 to 3, Examples 4, 6, and 7, it can be seen that as the water-binder ratio (the ratio of the mass of water to clay, industrial solid waste, and cement) decreases, the initial setting time of the grouting material is shortened. Therefore, in order to make the grouting material have a suitable initial setting time, the mass content of clay, industrial solid waste, cement, and water needs to be controlled within a reasonable range.
[0133] It can be seen from Examples 1 to 5 that as the mass content of clay decreases, the vertical expansion rate of the grouting material decreases; as the mass content of cement increases, the vertical expansion rate of the grouting material decreases; in order to make the grouting material have a suitable vertical expansion rate, the mass contents of clay and cement need to be controlled within a reasonable range.
[0134] In Comparative Example 1, the mass fraction of clay is less than 25 parts, the fluidity and initial setting time of the slurry finally prepared increase, the tensile bond strength decreases sharply, and the slurry no longer has the micro-expansion property.
[0135] In Comparative Example 2, the mass fraction of clay is greater than 35 parts and the mass fraction of industrial solid waste is less than 20 parts. The fluidity and initial setting time of the slurry are significantly reduced, which affects the construction performance in actual use and is not suitable for selection. When the specific gravity of the clay is greater than the specified range, the tensile bond strength no longer increases with the increase of the specific gravity.
[0136] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0137] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A grouting material, characterized in that: Calculated by mass, it includes the following components: 25 to 35 parts of clay, 20 to 30 parts of industrial solid waste, 5 to 15 parts of cement, 1 to 3 parts of gypsum, 5 to 10 parts of activator, 0.1 to 1 part of admixture, 1 to 5 parts of redispersible latex powder and 20 to 30 parts of water; Wherein, the industrial solid waste includes fly ash and granulated blast furnace slag powder.
2. The grouting material according to claim 1, characterized in that: Calculated by mass, it includes the following components: 25 to 30 parts of clay, 25 to 30 parts of industrial solid waste, 5 to 12 parts of cement, 1.5 to 2.5 parts of gypsum, 6 to 9 parts of activator, 0.4 to 1 part of admixture, 1 to 4 parts of redispersible latex powder and 23 to 30 parts of water.
3. The grouting material according to any one of claims 1 to 2, characterized in that: The clay includes one or more of kaolin and montmorillonite.
4. The grouting material according to any one of claims 1 to 2, characterized in that: The mass ratio of the fly ash to the granulated blast furnace slag powder is (1-3):
1.
5. The grouting material according to any one of claims 1 to 2, characterized in that: The cement includes one or more of ordinary Portland cement, Portland cement and rapid hardening sulphoaluminate cement.
6. The grouting material according to any one of claims 1 to 2, characterized in that: The gypsum includes hemihydrate gypsum.
7. The grouting material according to any one of claims 1 to 2, characterized in that: The activator includes one or more of sodium silicate and sodium carbonate; Optionally, the activator includes sodium silicate and sodium carbonate; Further optionally, the mass ratio of the sodium silicate to the sodium carbonate is (1-4):
1.
8. The grouting material according to any one of claims 1 to 2, characterized in that: The admixture includes one or more of a high-efficiency water reducing agent, a defoaming agent and a thickening agent; Optionally, the high-efficiency water reducer includes a polycarboxylate high-efficiency water reducer; Optionally, the defoaming agent includes a polyurethane defoaming agent; Optionally, the thickener comprises a polycarboxylate thickener.
9. A method for preparing a grouting material, characterized in that: The steps include: The grouting material is prepared by providing raw materials according to the components of the grouting material according to any one of claims 1 to 8, mixing them evenly, and obtaining the grouting material.
10. Use of the grouting material as described in any one of claims 1 to 8 in hollow repair.